Dietary Supplementation with a Combination of Lactoferrin, Fish Oil, and Enterococcus faecium WB2000 for Treating Dry Eye: A Rat Model and Human Clinical Study - Kawashima, Motoko; Nakamura, Shigeru; Izuta, Yusuke; Inoue, Sachiko; Tsubota, Kazuo (The ocular surface, 2016)
To examine the effect of a combined dietary supplement containing fish oil, lactoferrin, zinc, vitamin C, lutein, vitamin E, γ-aminobutanoic acid, and Enterococcus faecium WB2000 on dry eye. A preliminary study in a rat model and a prospective, randomized, double-blind, placebo-controlled study in humans were conducted. Forty Japanese volunteers aged 22 to 59 years were randomized into combined dietary supplement (2 capsules/day; 20 participants) and placebo (vehicle; 19 participants) groups and treated once daily for 8 weeks. Rats received the combined dietary supplement components (10 or 50 mg/kg orally) or vehicle (2% DMSO), and dry eye was mechanically induced for 2 days. Tear production was measured in rats after dry eye was induced. Humans were assessed at baseline and weeks 4 and 8 post-supplementation based on keratoconjunctival epithelial damage; fluorescein tear film breakup time; tear production; biochemical data; information regarding subjective dry eye symptoms by answering a questionnaire; and information regarding adverse events via medical interviews. Supplementation dose-dependently mitigated the decrease in tear production in rats. Among subjects with confirmed dry eye, clinical symptoms improved at weeks 4 and 8 more significantly in the supplementation group than in the placebo group (P<.05). The rate of increase in the Schirmer value was greater in the supplementation group. No adverse events occurred. Supplementation improved objective and subjective dry eye symptoms.